Analisis Putusan Mahkamah Konstitusi No. 36/PUU-XV/2017 Tentang Hak Angket Dewan Perwakilan Rakyat Terhadap Komisi Pemberantasan Korupsi - Bakri Iskandar (Universitas Islam Indonesia, 2019)
The issues raised in this article are first, examining the opinion of the Constitutional Court justices in the Constitutional Court Decision No. 36 / PUU-XV / 2017 and second, analyzing the implications of the Constitutional Court Decision No. 36.PUU-XV / 2017 against the existence of the KPK. The research is a normative legal study with the data collection methods of document study and analyzed by using the descriptive-qualitative methods. The results of this study indicate that, First, there are three different opinions in the Constitutional Court Decision No. 36 / PUU-XV / 2017. The first opinion, the KPK is in the realm of executive power so that the DPR has the right to exercise the right of inquiry to the KPK. In addition, until now there are no other state institutions that can control the KPK so that the DPR can use its questionnaire rights to carry out its supervisory functions. The second opinion is that the KPK is an independent state institution outside the legislative, judicial and executive powers. And the third opinion states that the KPK is in the realm of executives who are independent. So that the Parliament can not use the right of inquiry to the KPK. Second, the implication for the existence of the KPK is that the KPK's relationship with political power, especially in the parliament, is increasingly not ideal. Though the KPK was formed as an independent state institution. The relationship between the KPK and political power will be ideal if the election of the KPK chairperson is appointed by its own members and is no longer elected through the DPR.